Peroksidasi Lipid oleh Parasetamol dan Ekstrak Air Panas Teh Hijau (Camellia sisnensis ) pada Sel Khamir Candida tropicalis yang di Simpan pada Suhu Rendah - Julistiono, Heddy (Perhimpunan Biologi Indonesia, 2012)
ABSTRACTLipid Peroxidation by Paracetamol and Hot Water Extract of Green Tea (Camellia sinensis ) in Yeast Candida tropicalis preserved in Low Temperature. The use of C. tropicalis cell as a tool to evaluate antioxidant property of green tea to protect oxidative stress caused by paracetamol in cell level was investigated in our laboratory. Immediate availability of cell culture will significantly reduce the time of cell preparation. Low temperature preservation of cell culture is one of methods to produce cell cultures. However, low temperature might affectphysiological state of the cell. In this study, effect of low temperature preservation (4 ºC, 10 days) on the oxidative response of yeast cell treated with paracetamol and hot water extract of green tea had been investigated. Cells incubation with paracetamol 0.3 % for 2 h caused oxidative stress in both fresh and preserved culture since the content of a marker of oxidativestress, peroxyd lipids increased significantly. Whereas, concentration of peroxidised lipids in preserved cultures was lower than that of fresh culture. Increasing of peroxydized lipids followed with decreasing of cell viability in fresh culture but not in preserved culture. Green tea withconcentration of 0.1 % decreased peroxyd lipids in fresh cultures treated with paracetamol but not in preserved cultures. Green tea with concentration of 0.2 % or 0.4 % in increased peroxyd lipids in fresh cultures treated with paracetamol but not in preserved cultures. The data indicated that green tea did not show anti- or pro-oxidative effect in cultures preserved in low temperature treated with paracetamol. However, induction of super oxide dismutase (SOD), an antioxidant defense enzyme, was not observed in cell preserved in low temperature. The study revealedthat low temperature might make the cell more resistant against prooxidative properties of paracetamol.Keywords: C. tropicalis, oxidative stress, low temperature, paracetamol, green tea